Empirical Identification of Key Sectors in the Indian Economy - Hazari, Bharat R. (The Review of Economics and Statistics, 1970)
IN recent literature it has been generally asserted that key sectors play an important role in initiating the process of economic development and diversification of the industrial structure of the economy and that a substantial part of investment should be made in the key sectors. This paper is an attempt to identify key sectors empirically with the help of two alternative methods both based on the Leontief open static model (1) by defining key sectors purely in a technological manner as done by Rasmussen and Hirschman I and (2) by defining them with respect to the preference function of the planner, given the technological structure.